2001
DOI: 10.1159/000050190
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Findings in Patients with Gastric Adenocarcinoma with Familial Aggregation

Abstract: Background/Aims: The clinicopathological characteristics of gastric cancer (GC) with a positive family history of site-specific GC have not been well discussed. The aim of this study was to estimate the risk of familial aggregation of GC in a hospital-based case-control study and to analyze the clinicopathological characteristics of GC with familial aggregation of GC. Methods: Our series was comprised of 926 histologically confirmed patients with GC (588 males and 338 females) and 2,052 non-cancer outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…The lowest reported OR in Japan was 1.5 (95% CI 1.2 -1.8), based on a large study on 614 cases and 2444 hospital-based controls by Minami et al (2003). Ikeguchi et al (2001) studied 2025 cases of gastric cancer and 926 hospital-based controls. The familial OR was approximately 2 (RR ¼ 1.9; 1.6 -2.2).…”
Section: Worldwide Distribution Of Gastric Cancermentioning
confidence: 99%
“…The lowest reported OR in Japan was 1.5 (95% CI 1.2 -1.8), based on a large study on 614 cases and 2444 hospital-based controls by Minami et al (2003). Ikeguchi et al (2001) studied 2025 cases of gastric cancer and 926 hospital-based controls. The familial OR was approximately 2 (RR ¼ 1.9; 1.6 -2.2).…”
Section: Worldwide Distribution Of Gastric Cancermentioning
confidence: 99%
“…Some studies, although not all, showed that a family history of GC might be considered a stronger risk factor for women [2,3] , or that risk of GC might be higher for subjects with an affected sibling rather than a parent [13,15,16,21] . The risk of GC associated with family history for non-GC has been found with different cancers in different studies [5,10,15,21] . In addition, the histological type of FGC was pronounced for "intestinal" and/or "diffuse" cancers in different studies germline mutation of CDH1, has never been found in eastern Asia [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Family history of GC has previously been studied in many regions, including eastern Asian [2][3][4][5][6][7][8][9] , North American [10][11][12] , northern European [13][14][15] , and Mediterranean countries [16][17][18][19][20][21] . A much higher incidence of familial GC (FGC) was reported from Mediterranean countries [19] , while a relatively low occurrence was noted in northern European countries [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that a family history of stomach cancer was a stronger risk factor for women, 8,12,22,25 although the evidence is not consistent. 16 In some, 7,16,24 but not all 4,9,14 studies, the risk was higher for subjects with an affected sibling rather than a parent.…”
mentioning
confidence: 94%
“…Furthermore, the epidemiologic evidence is not consistent on the variation of familial risk according to the age at onset of gastric cancer. 8,11,14,16,22 Only a few studies have investigated the association of family history of other cancers and risk of stomach cancer, and yielded contrasting results. 2,[5][6][7]10,14,15 Associations have been reported with a family history of cancers of the breast, 15 brain/central nervous system, 2,6 female genital, 2,6 esophagus, 2 thyroid 2 and colon.…”
mentioning
confidence: 99%